Energy-Based Nonlinear Adaptive Control Design for the Quadrotor UAV System With a Suspended Payload - Yang, Sen; Xian, Bin (IEEE transactions on industrial electronics (1982), 2020)
In this paper, the control problem for an underactuated quadrotor unmanned aerial vehicle (UAV) with a suspended payload is investigated. An energy-based nonlinear controller is proposed that is able to control the quadrotor UAV's position and the payload's swing angle asymptotically. An adaptive control design is developed to compensate for the unknown length of the cable which is used to connect the UAV and the payload. The Lyapunov-based stability analysis is employed together to prove the stability of the closed-loop system. Detailed real-time experimental results illustrate the good performance of the proposed controller.